The Relationship between Blood Flow Velocity (QB) and Achievement of URR Values in Hemodialysis Patients - Christianto Napitu; Lia Natalia; Yovita Setiyowati (Lembaga Pengembangan Kinerja Dosen, 2025)
This literature study examines the relationship between blood flow velocity (Qb) and the achievement of Urea Reduction Ratio (URR) values in chronic kidney disease (CKD) patients undergoing hemodialysis. The main objective of this review is to identify and analyze findings from various studies related to this topic. The research method used is a systematic literature review, with article searches through the ResearchGate, Proquest, and Google Scholar databases using specific keywords. Of the 310 initial articles, 10 articles that met the inclusion and exclusion criteria were further analyzed. The results of the analysis of the 10 articles showed a variety of findings regarding the relationship between Qb and URR. Three studies showed a significant relationship between increasing Qb with increasing URR and hemodialysis effectiveness. Meanwhile, two other studies found no significant relationship between Qb and hemodialysis adequacy, emphasizing the role of other factors such as vascular access patency, body weight, and dialysis characteristics. Other studies also highlighted the influence of dialysis filter type and hemodialysis time on adequacy. The conclusion of this literature review is that there is an indication of a positive relationship between blood flow velocity and achievement of hemodialysis adequacy as measured by URR in CKD patients. However, this relationship is influenced by various other factors. The implication of this review is the need for holistic consideration of patient and technical factors in determining Qb settings to achieve optimal dialysis adequacy. Further research is needed to identify more specific and personalized guidelines in Qb settings to improve hemodialysis outcomes in CKD patients